The Role of Commerce in the Growth of Towns In Central Highland Ecuador 1750-1920 - Bromley, Rosemary (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
Commerce was a key function of urban development in the Central Highlands of Ecuador. Three towns—Latacunga, Ambato, and Riobamba—are examined in some detail in order to understand why commercial functions developed more strongly in some towns than in others. A dynamic and prosperous agricultural hinterland was the key to growth. Ambato grew faster than the other towns because its hinterland, fairly densely populated by white smallholders, participated more readily in cash-crop production than did the Indian population surrounding the other towns.